Translation and evaluation of the simplified Chinese version of the rating form of IBD patient concerns - Jianfeng Luo; Jiamin Zhong; Haiwen Li; Shijing Zhang; Liwan Zhang; Jiang-tao Hou; Junyu Ke; Huibiao Li; Fengbin Liu; Xin-lin Chen (BMC Gastroenterology, 2022)
Abstract Background Inflammatory bowel disease (IBD) has become a global public health problem. The prevalence of IBD in China increased annually in past two decades. Methods This study was to translate and validate the rating form of IBD patients' concerns (RFIPC), and to describe disease-related worries and concerns of patients with IBD. The simplified Chinese version of the RFIPC was developed according to translation and back-translation procedure. Patients with IBD were consecutively enrolled from the First Affiliated Hospital of Guangzhou University of Chinese Medicine. The participants were assessed using the RFIPC and the Short Inflammatory Bowel Disease Questionnaire (SIBDQ). Internal consistency, test–retest reliability, measurement error, confirmatory factor analysis (CFA) and correlation of the RFIPC with the SIBDQ were performed to evaluate the psychometric characteristics of the RFIPC. Results A total of 116 patients with IBD, 73 with ulcerative colitis (UC) and 43 with Crohn’s disease (CD), were enrolled in this study. Thirty-seven of them recompleted the questionnaires for the second time between 7 and 14 days after the first interview. The results of CFA indicated the original structure of the RFIPC was reasonable. Cronbach's alpha value of the RFIPC were 0.97. The intraclass correlation coefficients of four domains ranged from 0.85 to 0.92. The standard error of measurement was 7.10. The correlation coefficients between total score of the RFIPC and the SIBDQ score ranged from − 0.54 to − 0.70. Median total score of the RFIPC was 39.4 (IQR 24.0–59.3). Patients with severe symptoms reported higher scores of the RFIPC. The uncertain nature of disease, having surgery, having an ostomy bag, developing cancer, feeling out of control, being a burden on others and financial difficulties were highest concerns of patients with IBD. Comparing with patients with UC, patients with CD had more concerns of the ability to have children and being treated as different (P < 0.05). Conclusions The simplified Chinese version of RFIPC is a valid and reliable tool. It could be used for assessing disease-related worries and concerns of patients with IBD in China. Specific concerns of patients with UC and CD are different, therefore, health workers should consider the specific needs of UC and CD patients.